Komposisi Tari Bunga di Atas Karang - DARMAWAN DADIJONO (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
The Composition of “Flower on Coral” Dance is about a transformational phenomenon realized into adance called “Flower on Coral.” An art performance cannot be separated from its stage since it is an importantand integrated part of the art performance itself. Space of the performance becomes the main convention tobuild artistic communication between the star and the audience. Choices of the staging form are not just forbuilding physical distance but also building spirit. The ritual aspect of the dance is dealt by the presence of an artperformance. Humans’ art which becomes inseparable part of the nature is expected to raise new religious spacefor the humans to believe in God. ‘Walk by the Cross’ is a Catholic tradition used to improve humans’ spiritual life.Many Catholics do this tradition just as Jesus Christ did. So, there are many places built for religious visits and toexperience the passion of Christ harder before He died.